Portable, bedside, low-field magnetic resonance imaging for evaluation of intracerebral hemorrhage - Mercy H. Mazurek (Nature Portfolio, 2021)
Conventional magnetic resonance imaging (MRI) operates at a high magnetic field strength and requires a strict access-controlled environment, making MRI often inaccessible. Here, the authors present a portable low-field MRI device that detects intracerebral hemorrhage with high accuracy.